Anderson and Authoritarianism - Thiele, Steven (The Australian journal of anthropology, 1992)
This paper examines the work of John Anderson with particular reference to the issue of authority, or, more precisely, authoritarianism. It is suggested that opposition to authoritarianism, along with an attempt to spell out a non-authoritarian form of social enquiry, is Anderson's central concern. In the light of this, a number of reasons are put forward as to why his work has not been taken up by many sociologists and anthropologists. Finally, a suggestion is made as to how his thinking might be challenged in a way sufficient to stimulate its development. This is done by reference to a distinction between guilt, an emotion and set of practices powerful where appeal to authority is important, and shame, which does not require such an appeal.